Why regulators assess risk differently: Regulatory style, business organization, and the varied practice of risk‐based food safety inspections across the EU. Issue 1 (19th May 2020) - Borraz, Olivier; Beaussier, Anne‐Laure; Wesseling, Mara; Demeritt, David; Rothstein, Henry; Hermans, Marijke; Huber, Michael; Paul, Regine
Abstract: This article advances scholarship on comparative regulation by moving beyond the conventional focus on formal law and EU comitology to assess the extent of 'practice convergence' in the implementation of EU regulation. Drawing on 50 key informant interviews, a survey, and policy document analysis, we compare how regulators in England, Germany, France and the Netherlands have implemented EU requirements that food safety inspections be 'risk‐based'. Focusing on a clear dependent variable – risk‐scoring methods – we find important differences in the conception and targeting of risk‐based inspections; with starkly different implications for what kind of food businesses they need to target to ensure safety within an ostensibly harmonized single market. We attribute variation in the implementation of risk‐based inspection to the ways that EU requirements were filtered through long‐entrenched regulatory styles and modes of food business organization in each country, reinforcing preexisting inspection practices in the design of new risk‐based tools.